Potential of Quantum Computing for supply chain management - A systematic literature review - Zhang, Jiayue (Cranfield University, 2025)
Purpose: This study explores the transformative potential of quantum computing (QC) in supply chain management (SCM), addressing the growing complexity of logistics, operations, and security where classical optimisation methods reach their limits. Research method: A systematic literature review (SLR) was conducted, covering studies from 2015–2025 in Scopus and Web of Science. Following PRISMA screening, 61 articles were analysed using descriptive mapping and thematic synthesis. Findings: The review identifies a three stage, adoption pathway awareness, pilot projects, and integration, which driven by computational efficiency, enhanced security, scalability, and potential cost-effectiveness. Current applications concentrate on logistics, scheduling, inventory management, and quantum-secure systems, though most remain at proof-of-concept level. Adoption is constrained by technological immaturity, integration complexity, high costs, and skills shortages. Contribution: The study consolidates fragmented insights into QC and SCM, develops a conceptual adoption framework linking drivers, barriers, and implementation stages, and provides theoretical and practical guidance for researchers, managers, and policymakers. It highlights QC’s potential to improve efficiency, resilience, and sustainability of supply chains. Limitations: The review is limited by the small pool of relevant literature, the dominance of conceptual and pilot-level studies, and the exclusion of grey and non-English sources. Sector-specific variations and technical-economic evaluations remain underexplored, requiring further empirical research.
Keywords: Quantum computing; systematic literature review; conceptual framework; digital supply chains; supply chain management; logistics